Inferior vena cava filter insertion through the popliteal vein: enabling the percutaneous endovenous intervention of deep vein thrombosis with a single venous access approach in a single session - Hyoung Ook Kim; Jae Kyu Kim; Jin Gyoon Park; Nam Yeol Yim; Yang Jun Kang; Hye Doo Jung (Diagnostic and Interventional Radiology, 2016)

(untitled)
PURPOSE:We aimed to evaluate the efficiency of placing an inferior vena cava (IVC) filter through the same popliteal vein access site used for percutaneous endovenous intervention in patients with extensive lower extremity deep vein thrombosis.METHODS:This retrospective study included 21 patients who underwent IVC filter insertion through the popliteal vein over a three-year period. Patient medical records were reviewed for the location of the deep vein thrombosis, result of filter removal, and total number of endovascular procedures needed for filter insertion and recanalization of the lower extremity venous system. Follow-up lower extremity computed tomography (CT) venography was also reviewed in each patient to assess the degree of filter tilt in the IVC.RESULTS:All patients had extensive lower extremity deep vein thrombosis involving the iliac vein and/or femoral vein. Seventeen patients showed deep vein thrombosis of the calf veins. In all patients, IVC filter insertion and the recanalization procedure were performed during a single procedure through the single popliteal vein access site. In the 17 patients undergoing follow-up CT, the mean tilt angle of the filter was 7.14°±4.48° in the coronal plane and 8.77°±5.49° in the sagittal plane. Filter retrieval was successful in 16 of 17 patients (94.1%) in whom filter retrieval was attempted.CONCLUSION:Transpopliteal IVC filter insertion is an efficient technique that results in low rates of significant filter tilt and enables a single session procedure using a single venous access site for filter insertion and percutaneous endovenous intervention.